Principles and practice of particle therapy - Malouff, Timothy D.; Trifiletti, Daniel M. (Hoboken, NJ : John Wiley & Sons, 2022)
"While the fundamental physical principles that provide the basis for particle therapy are well established, the practical use of these principles is continually evolving as the use of particle therapy continues to grow. Once a novelty, particle therapy is now widely available in many parts of the world. Proton therapy is now a routine option for many patients, and multiple facilities in different countries are treating patients with carbon ion therapy as data is gathered to determine the best clinical use of this technology. Pharmaceutical improvements have also revitalized neutron beam therapy when used for boron neutron capture therapy (BNCT), joining several fast neutron therapy (FNT) centers around the world. Compared to traditional photon and electron radiation therapy, heavier particles have some desirable physical characteristics that allow for safer and more effective treatments in certain scenarios. Heavier particles such as neutrons, protons, and carbon ions offer increased linear energy transfer (LET) and relative biological effectiveness (RBE). Heavier charged particles have beneficial dosimetric advantages such as decreased distal, lateral, and integral dose, and neutron beams can be used to generate targeted therapeutic secondary particles."--
Keywords: Radiotherapy; Radiotherapy; Electronic books